Exploring the Impact of Individualized Research Consultations Using Pre and Posttesting in an Academic Library: A Mixed Methods Study - Sikora, Lindsey; Fournier, Karine; Rebner, Jamie (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective – Academic librarians consistently offer individualized help to students and researchers. Few studies have empirically examined the impact of individualized research consultations (IRCs). For many librarians, IRCs are an integral part of their teaching repertoire. However, without any evidence of an IRC’s effectiveness or value, one might ask if it’s worth investing so much time and effort. Our study explored the impact of IRCs on students' search techniques and self-perceived confidence levels. We attempted to answer the following questions: 1) Do IRCs improve students’ information searching techniques, including the proper use of keywords and/or subject headings, the accurate use of Boolean operators, and the appropriate selection of specialized resources/databases? 2) Do IRCs influence students’ confidence level in performing effective search strategies?Methods – Our study used a mixed-methods approach. Our participants were students from the Faculties of Health Sciences and Medicine at the University of Ottawa, completing an undergraduate or graduate degree, and undertaking a research or thesis project. Participants were invited to complete two questionnaires, one before and one after meeting with a librarian. The questionnaires consisted of open-ended and multiple choice questions, which assessed students' search techniques, their self-perceived search techniques proficiency and their confidence level. A rubric was used to score students' open-ended questions, and self-reflective questions were coded and analyzed for content using the software QSR NVivo.Results – Twenty-nine completed pre and posttests were gathered from February to September 2016. After coding the answers using the rubric, two paired-samples t-tests were conducted. The first t-test shows that students’ ability to use appropriate keywords was approaching statistical significance. The second t-test showed a statistically significant increase in students’ ability to use appropriate search strings from the pretest to the posttest. We performed a last paired-samples t-test to measure students’ confidence level before and after the appointment, and a statistically significant increase in confidence level was found.Conclusion – Out of three paired t-tests performed, two showed a statistically significant difference from the pretest to the posttest, with one t-test approaching statistical significance. The analysis of our qualitative results also supports the statement that IRCs have a positive real impact on students’ search techniques and their confidence levels. Future research may explore specific techniques to improve search strategies across various disciplines, tips to improve confidence levels, and exploring the viewpoint of librarians.